2023
DOI: 10.1021/acs.analchem.3c04710
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Electrochemiluminescence of Zirconium Metal–Organic Framework as a Single Luminophore for Sensitive Detection of HPV-16 DNA

Gaoxu Chen,
Wenjie Dai,
Congyi Hu
et al.

Abstract: This study developed a new zirconium metal− organic framework (MOF) luminophore named Zr-DPA@TCPP with dual-emission electrochemiluminescence (ECL) characteristics at a resolved potential. First, Zr-DPA@TCPP with a core− shell structure was effectively synthesized through the self-assembly of 9,10-di(p-carboxyphenyl)anthracene (DPA) and 5,10,15,20tetra(4-carboxyphenyl)porphyrin (TCPP) as the respective organic ligands and the Zr cluster as the metal node. The reasonable integration of the two organic ligands D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…For Ni/Co−MOF−TCPP−Fc, the absorption peak of TCPP at 1270 cm −1 was weakened, indicating that the hydrogen on −OH was replaced by metal ions and formed an Me−O bond. The reduction in peak intensity at 1600 and 1690 cm −1 was possibly attributed to alterations in the electronic structure that occurred when porphyrin was incorporated as a ligand within the MOF [ 37 , 38 ]. A broad absorption band was observed for the pure substance of Fc−COOH between 3310~2500 cm −1 due to the O−H stretching vibration of the carboxyl group in Fc−COOH, and a stretching vibration peak of the C=C in cyclopentadiene was observed at 1475 cm −1 [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…For Ni/Co−MOF−TCPP−Fc, the absorption peak of TCPP at 1270 cm −1 was weakened, indicating that the hydrogen on −OH was replaced by metal ions and formed an Me−O bond. The reduction in peak intensity at 1600 and 1690 cm −1 was possibly attributed to alterations in the electronic structure that occurred when porphyrin was incorporated as a ligand within the MOF [ 37 , 38 ]. A broad absorption band was observed for the pure substance of Fc−COOH between 3310~2500 cm −1 due to the O−H stretching vibration of the carboxyl group in Fc−COOH, and a stretching vibration peak of the C=C in cyclopentadiene was observed at 1475 cm −1 [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lu et al reported a sandwich-type ECL immunosensor based on Zr 6 -5,10,15,20-tetrakis (4-carboxyphenyl) porphyrin framework (PCN-224) for the determination of cardiac troponin I . Li’s team proposed a new zirconium metal–organic framework (Zr-DPA@TCPP) as a single luminophore, which showed synchronous anodic and cathodic ECL signals . Chen et al exploited a cage-like porous complex as the microreactor to attenuate the aggregation-caused quenching effect of meso-tetra­(4-carboxyphenyl) porphine .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Lei’s team developed the m-MOF integrated with two ligands, with DPA as a luminophore and D-H2 as an intramolecular coreactant, which generated ECL without exogenous coreactants . Our group not only prepared a dual-ligand Zr-DPA@TCPP MOF, which displayed dual ECL emission at the cathode and anode, but also developed Zn-MOF with Hcptpy as the ligand which realized coreactant-free and dual-emission ECL . However, there are still disadvantages of low ECL efficiency.…”
Section: Introductionmentioning
confidence: 99%